2017
DOI: 10.3171/2016.4.jns152600
|View full text |Cite
|
Sign up to set email alerts
|

Blunt cerebrovascular injuries in severe traumatic brain injury: incidence, risk factors, and evolution

Abstract: OBJECTIVE Blunt cerebrovascular injuries (BCVIs) affect approximately 1% of patients with blunt trauma. An antithrombotic or anticoagulation therapy is recommended to prevent the occurrence or recurrence of neurovascular events. This treatment has to be carefully considered after severe traumatic brain injury (TBI), due to the risk of intracranial hemorrhage expansion. Thus, the physician in charge of the patient is confronted with a hemorrhagic and ischemic risk. The main objective of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 33 publications
3
84
1
1
Order By: Relevance
“…Similarly, in a population-based study by Macciocchi and colleagues, 60% of patients with a traumatic spinal cord injury had a co-occurring TBI [24]. Paraplegic patients with severe TBI had lower FIM™ motor scores and a longer LOS in rehabilitation, compared to those without TBI or mild TBI [25]. Additional injury to the peripheral nerves occurs in approximately 34% of patients with severe TBI [26].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a population-based study by Macciocchi and colleagues, 60% of patients with a traumatic spinal cord injury had a co-occurring TBI [24]. Paraplegic patients with severe TBI had lower FIM™ motor scores and a longer LOS in rehabilitation, compared to those without TBI or mild TBI [25]. Additional injury to the peripheral nerves occurs in approximately 34% of patients with severe TBI [26].…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Typically, these ischemic infarcts occur between 10 and 72 hours after the injury. 7,34 Arterial transection can cause exsanguination and AVF. Patients with AVFs can have symptoms related to increased venous pressure or steal phenomenon.…”
Section: Bcvi Mechanism and Pathophysiologymentioning
confidence: 99%
“…Controversy exists concerning the necessity of anticoagulation treatment following blunt traumatic vertebral artery injuries and their associated bleeding risks in those requiring spinal surgery. 8 Studies have shown better neurologic outcomes in patients who received anticoagulation treatment for cerebrovascular injury before symptoms arise. 1,8 Treating patients early with an anticoagulant has been shown to prevent progression to stroke or ischemia in patients with cerebrovascular (vertebral or carotid artery) injury.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,7 Cerebrovascular injury can lead to neurovascular complications either from thrombus formation at the tear site or narrowing of the vessel. 8 Anticoagulation treatment begun in the early period (before the onset of stroke symptoms) has been shown to improve mortality and lower neurologic complications, but in patients having spinal surgery it carries the risk of epidural hematoma and major bleeding. [8][9][10][11] Although some studies provide recommendations as to when spine surgery patients should receive prophylaxis postoperatively to prevent deep vein thrombosis, 9,[12][13][14] few directly discuss the outcomes in patients who are actively receiving anticoagulation treat-ment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation